Anxiety Among Retiring Employees in the Workplace - Mohd. Rashid, Faridah Hanam (2000)
Retiring employees are facing problems during the transition period from work to retirement. The loss of job roles, financial insecurity, poor health, dissatisfaction in life, loss of social support and self-esteem as a result of retirement were among the factors that lead to the feelings of anxiety among retiring employees. The purpose of the study was to examine the factors that influence anxiety among retiring employees undergoing transition from work to retirement and to identify the levels of anxiety among employees of different occupational status and gender. Since work performance is an important factor in an organization, the study also examined the relationship between anxiety and the employee's performance in the workplace. A sample size of 238 respondents was obtained from a population of 610 retiring employees of 14 agencies under the Ministry of Agriculture and Ministry of Rural Development of Malaysia. A self-administered questionnaire was used as a mode of data collection. All instruments used in the hypotheses testing were adapted from previously developed instruments, except the one for the variable performance which was constructed by the researcher. Reliability, Frequencies, Pearson's Product Moment Correlation, t - test and Multiple Regression Analysis were used in the analysis. The findings indicated that financial insecurity, life satisfaction and social support were negatively related to pre-retirement anxiety. No significant relationships were found between anxiety and health status, self-esteem, the loss of work role and performance. The study also indicated that there was no significant difference in anxiety between higher and lower occupational status, as well as between male and female employees. Financial insecurity, health status, life satisfaction, self esteem, loss of work role and social support contributed to the variation in anxiety.